The development of lemma and meaning in the language variety used by adolescents on social media - Fitri Amilia; Indah Werdiningsih; Rohmad Tri Aditiawan (BAHASTRA, 2022)
This study examines the natural phenomena on the development of lemma and meaning in the variety of languages used by adolescents on social media. Research design was done naturally through the process of observation, taking notes, and writing down the case. The qualitative research appears in the development of the entry which is easily found as a definite phenomenon of linguistic development. The data collection method was carried out by tracing data on the use of various languages on social media. To analyze the data, the researcher uses padan and agih methods. This method is to test the accuracy of classification on the types of language used by adolescents in social media in the development of the entry and or the development of the meaning of the entry. The results showed that the variety of languages on social media is very dynamic, developing, arbitrary, but conventional. The variety of languages indicates the development of new lemmas, acronyms, and walikan. The development of meaning is marked along with the development of the entry in the form of synonyms and the use of the Indonesian language entry in the form of a polysemic. Based on the results of this study, adolescents can be considered a productive period in exploring the language, through direct interaction or social media. Becoming actively productive in language exploration led to a potential for concepting a new lemma and a new meaning according to the context of language use. In addition, this development becomes one proof of the self-existence of adolescence, community characteristics, and also the need for the development of Indonesian vocabulary.